European climate pact citizen volunteers: strategies for deepening engagement and impact - Tosun, Jale; Pollex, Jan; Crumbie, Laurence (Policy design and practice, 2023)
The European Climate Pact is one constitutive element of the European Green Deal, which has the ambition of making the European Union (EU) climate neutral by 2050. It is a particularly intriguing measure since it is designed as a format for volunteering, known as European Climate Pact Ambassadors, whom the EU Commission expects to inform members of their communities and networks about climate change and to inspire and support climate action. Each Pact Ambassador is presented on a dedicated website hosted by the EU Commission, which means that this programme is highly personalized. With this paper, we address Pact Ambassadors who do not work as policy professionals and strive to offer them guidance on navigating their mandate. In essence, we invite them to personalize the mandate and to assume those roles and carry out those activities that they feel comfortable with and which align with the overarching goals and principles of the ambassadors’ programme.